Fast-track recovery after major liver and pancreatic resection from the nursing point of view. - Kapritsou, Maria; Korkolis, Dimitrios P; Giannakopoulou, Margaret; Kaklamanos, Ioannis; Elefsiniotis, Ioannis S; Mariolis-Sapsakos, Theodoros; Birbas, Konstantinos; Konstantinou, Evangelos A (Gastroenterol Nurs, 2014)
Postoperative fast-track recovery protocols combine various methods to support immediate care of patients who undergo major surgery. These protocols include control of postoperative pain and early beginning of oral diet and mobilization. The combination of these approaches may reduce the rate of postoperative complications and facilitate hospital discharge. The aim of this study was to evaluate progress and parameters of fast-track recovery after major liver and pancreatic resection. A descriptive bibliographical review from 2001 to 2012 via electronic databases such as MEDLINE, PubMed, and Google Scholar was undertaken. Articles that focused on a fast-track protocol were studied. Reports focusing on the implementation of a fast-track protocol in the postoperative recovery of patients after major hepatectomy or pancreatectomy were selected. Fast-track protocols may be applicable to patients recovering after major liver or pancreatic resection. Future research should be focused on particular parameters of the fast-track protocol separately.
Keywords: Critical Pathways; Diet Therapy; Early Ambulation; Hepatectomy; Humans; Length of Stay; Liver Neoplasms; Pancreatectomy; Postoperative Care; Randomized Controlled Trials as Topic; Recovery of Function; Treatment Outcome